Nutrient leaching in soil applied with Bio-Organic Fertilizer (BOF) / Siti Junaidah Ma’mun - Ma’mun, Siti Junaidah (Faculty of Plantation and Agrotechnology, 2017)
Plants nutrients are essential for the production of oil palm. In order to achieve the nutrient uptake maximization by the palms, the need of fertilizer is vital for optimum growth and high production. Bio- organic fertilizer has its benefit in term of increasing the nutrient uptake to palm. The aim of this study was to to determine the water-soluble and exchangeable K, Ca and Mg for leaching potential and plant uptake with the addition of Bio-organic fertilizer (BOF) in soil. The soil sample was taken at Felcra Nasaruddin Estate. The experiment consists of ; control (T0) and soil mixed with BOF (T1). Both treatments were leached in the leaching tube with two types of extractant; distilled water (S1) and ammonium acetate (S2). Each sample was replicated three times. Leachate was collected after two days. After the treatments left react with the extractants, the study demonstrates that the amount of treatment leached based on 95% CI of the mean are as following: T0S1; K= 105.8 mg/kg, Ca= 245.07 mg/kg, Mg= 45.3 mg/kg; T1S1; K= 491.4 mg/kg, Ca= 2045.33 mg/kg, Mg= 215.9 mg/kg; T0S1; K= 578.1 mg/kg, Ca= 192.3 mg/kg, Mg= 47.43 mg/kg; T1S2; K= 1178.33 mg/kg, Ca= 1621.67, Mg= 219 mg/kg. The nutrients that leached out from the application of BOF as a result is Ca> K> Mg. The study shows that BOF could be used as an effective nutrient resupply to the oil palm in alkaline soil condition where it shows the nutrients replacing to achieve an optimum good soil pH.